Le Problème de l’ornement chez Cellini : théorie, iconographie et humanisme - Trottein, Gwendolyn (RACAR : Revue d'art canadienne / Canadian Art Review, 2000)
This essay attempts to answer three intimately connected and fundamental questions regarding the art of Benvenuto Cellini (1500–71). Is a coherent theory of the arts discernible in his literary and plastic oeuvre? Further, what place is accorded ornament in this theory? And, finally, what philosophical positions are inherent in Cellini’s largely implicit theory of the arts? The Cellinian art theory which emerges from his apparently silent artworks, his seemingly narrative autobiography, and his predominantly empirical treatises provides an alternative to the Vasarian model promulgated in Cinquecento Florence and nineteenth- and twentieth-century art history. Downplaying the role of disegno and of spiritualizing neo-platonism, Cellini insists on an “ornamental” aesthetic that is grounded not so much in the visions and nightmares of a divinely inspired artistic imagination as in the experience and action of a willfol and all-too-human master goldsmith and sculptor. His theory is gendered and hierarchical, imposing male mastery on female matter, setting free-standing sculpture and goldsmithery at the top of a pyramid of the arts with drawing and painting relegated to its base.